Occupational Match Quality and Gender over Two Cohorts - John T. Addison; Chen Liwen; Orgul Demet Ozturk (Center for Economic Studies and ifo Institute (CESifo), 2018)
Using a multi-dimensional measure of occupational mismatch, we report distinct gender differences in match quality and changes in match quality over the course of careers. A substantial portion of the gender wage gap stems from match quality differences among more educated individuals. College-educated females are significantly more mismatched than males. Individuals with children and in more flexible occupations also tend to be more mismatched. Again, this is especially true of women. Cohort effects are also discernible: college-educated males of the younger cohort have lower match quality than the older cohort, even as the new generation of women is doing better.
Keywords: J13; J16; J22; J23; J24; J31; J33; J38; 330; multidimensional skills; occupational mismatch; match quality; wages; gender wage gap; fertility; fertility timing